Salzburg Festival 1937, Sixth Festival Concert, Sunday, August 22, 1937, directed by Bruno Walter - Salzburger Festspiele (1937 : Salzburg, Austria):::Contributor:::::::::::: (Kiesel; Salzburg; Austria, 2020)
Program for a performance by the Vienna Philharmonic under the direction of Bruno Walter of Beethoven's First Symphony, op. 21, and Bruckner's Eighth Symphony. Includes program notes in German, English, and French.